Exploring Instructors’ Beliefs about and Practices in Promoting Students’ Critical Thinking Skills in Writing Classes (GIST – Education and Learning Research Journal, 2023)
The study investigated instructors’ beliefs about and practices in promoting students’ critical thinking (CT) in writing classes. A multiple case study design was employed to address the objective of the study. Three instructors were purposively selected from Wolkite University and participated in the study. The instruments used for data gathering were classroom observation, interview and document analysis. The data were qualitatively analyzed using a grounded theory approach- open coding, axial coding, and selective coding. The findings showed that the participants interpreted CT as the students’ abilities to use appropriate language and logically argue in their writing. The interview data further revealed that promoting students’ CT skill can be facilitated through providing them with an explicit introduction to CT, incorporating CT into their evaluation system, and giving them meaningful topics and adequate opportunities to practice writing. Writing activities such as argumentative, summary, and cause-effect types were noted to promote students’ critical thinking in writing classes. The study categorized and reported factors that interfered with teachers’ beliefs and their practices as student-related, instructor-related and situation-specific factors.
Keywords: Critical thinking; instructors’ beliefs; instructors’ practices; students’ critical thinking; writing skills